Elevated systemic inflammation response index is associated with poor outcomes in minor ischemic stroke - Li, Jie; Zhang, Ping; Chen, Hong; Wang, Yanfen; Han, Yangyun; Wang, Chun; Yi, Xingyang (Frontiers in Neurology, 2024)
ObjectivesPatients with minor ischemic stroke (MIS) have substantial disability rates at 90 days. Our study aimed to explore the association between the systemic inflammation response index (SIRI) and 3-month functional outcomes in patients with MIS.MethodsWe conducted a prospective observational study in patients with MIS [defined as a National Institutes of Health Stroke Scale (NIHSS) score of 0–3] admitted within 24 h from symptoms onset. Blood samples for the SIRI measurement were collected on admission. The primary outcome measure was poor outcomes at 90 days (defined as a modified Rankin Scale score of 2–6). Univariate and multivariate logistic analyses were performed to assess the association between the SIRI and the risk of 3-month poor outcomes.ResultsA total of 152 patients with MIS were enrolled, of which 24 cases (15.8%) had poor outcomes at 90 days. The median SIRI level was 1.27 [interquartile range (IQR), 0.77–1.92, ×10^9 /L] on admission. MIS patients with poor outcomes had higher levels of the SIRI than patients with good outcomes (poor outcomes: median, 1.93, IQR: 1.17–3.28, ×10^9 /L; good outcomes: median, 1.21, IQR: 0.71–1.80, ×10^9 /L; p = 0.003). The high SIRI level group (SIRI >1.27 × 10^9 /L) had significantly higher rates of poor outcomes at 90 days (22.4% vs. 9.2%, p = 0.026). After adjusting for age, baseline NIHSS score, prehospital delay, Trial of Org 10,172 in Acute Stroke Treatment (TOAST) classification, and other confounders in multivariate analyses, an elevated SIRI level remained independently associated with an increased risk of poor outcomes in patients with MIS [odds ratio (OR): 1.57, 95% confidence interval (CI): 1.12–2.20; p = 0.010]. Meanwhile, a high level of the SIRI (>1.27 × 10^9/L) was still an independent risk factor for 3-month poor outcomes (OR: 4.80, 95%CI: 1.51–15.29; p = 0.008) in MIS patients.ConclusionDisability at 90 days was common in patients with MIS. An elevated SIRI was associated with poor outcomes in MIS patients. The SIRI might be a promising biomarker candidate that can help identify high-risk MIS patients with poor outcomes for reaching individual therapeutic decisions in clinical trials.